Inflammation and autoimmunity are interrelated in patients with sickle cell disease at a steady-state condition: implications for vaso-occlusive crisis, pain, and sensory sensitivity - Li, Wei; Pucka, Andrew Q.; Debats, Candice; Reyes, Brandon A.; Syed, Fahim; O’Brien, Andrew R.W.; Mehta, Rakesh; Manchanda, Naveen; Jacob, Seethal A.; Hardesty, Brandon M.; Greist, Anne; Harte, Steven E.; et al. (Frontiers in Immunology, 2024)
This study aimed to comprehensively analyze inflammatory and autoimmune characteristics of patients with sickle cell disease (SCD) at a steady-state condition (StSt) compared to healthy controls (HCs) to explore the pathogenesis of StSt and its impact on patients' well-being. The study cohort consisted of 40 StSt participants and 23 HCs enrolled between July 2021 and April 2023. StSt participants showed elevated white blood cell (WBC) counts and altered hematological measurements when compared to HCs. A multiplex immunoassay was used to profile 80 inflammatory cytokines/chemokines/growth factors in plasma samples from these SCD participants and HCs. Significantly higher plasma levels of 35 analytes were observed in SCD participants, with HGF, IL-18, IP-10, and MCP-2 being among the most significantly affected analytes. Additionally, autoantibody profiles were also altered, with elevated levels of anti-SSA/Ro60, anti-Ribosomal P, anti-Myeloperoxidase (MPO), and anti-PM/Scl-100 observed in SCD participants. Flow cytometric analysis revealed higher rates of red blood cell (RBC)/reticulocyte-leukocyte aggregation in SCD participants, predominantly involving monocytes. Notably, correlation analysis identified associations between inflammatory mediator levels, autoantibodies, RBC/reticulocyte-leukocyte aggregation, clinical lab test results, and pain crisis/sensitivity, shedding light on the intricate interactions between these factors. The findings underscore the potential significance of specific biomarkers and therapeutic targets that may hold promise for future investigations and clinical interventions tailored to the unique challenges posed by SCD. In addition, the correlations between vaso-occlusive crisis (VOC)/pain/sensory sensitivity and inflammation/immune dysregulation offer valuable insights into the pathogenesis of SCD and may lead to more targeted and effective therapeutic strategies.